Achieving comparable perfusion results across vendors. The next step in standardizing stroke care: a technical report. (22nd May 2019) - Bathla, Girish; Limaye, Kaustubh; Policeni, Bruno; Klotz, Ernst; Juergens, Markus; Derdeyn, Colin
Abstract : Background: The role of mechanical thrombectomy in acute ischemic stroke (AIS) has been further expanded by recent trials which relied on the results of CT perfusion (CTP) imaging. However, CTP parameters for ischemia and infarct can vary significantly across different vendors. Methods: We compared the outcomes of the Siemens CTP software against the clinically validated RAPID software in 45 consecutive patients with suspected AIS. Both perfusion softwares initially processed images using vendor defined parameters for hypoperfusion and non-viable tissue. The software thresholds on the Siemens software were decrementally altered to see if concordant results between softwares could be attained. Results: At baseline settings, the mean values for core infarct and hypoperfusion were different (mean of 30/69 mL, respectively, for RAPID and 49/77 mL for Siemens). However, reducing the threshold values for the later software showed a concordance of values at a relative cerebral blood flow <20%, with resulting core infarct and hypoperfusion volumes at 31/69 mL, respectively, for the Siemens software. A Wilcoxon paired test showed no significant difference between the calculated core infarct and hypoperfusion values, both for the entire population as well as for the subgroup of patients with large vessel occlusion. Conclusion: Equivalent CTP results between vendor softwares may be attainable by altering the thresholds for hypoperfused and non-viable tissue, despite differences in acquisition techniques, post-processing, and scanners.